IMPLEMENTATION OF EARLY INITIATION OF BREASTFEEDING IN NEWBORNS FOR THE PREVENTION OF HYPOTHERMIA IN THE WORKING AREA OF PAKKAT COMMUNITY HEALTH CENTER, PAKKAT DISTRICT, HUMBANG HASUNDUTAN REGENCY, NORTH SUMATRA PROVINCE, 2024 - Oktaviany, Mia; Simamora, Lasria; Pasaribu, Riska Susanti; Panjaitan, Polmaria Metawati; Imran, Ali (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background: Hypothermia is one of the leading causes of morbidity and mortality in newborns due to the inability of neonates to maintain body temperature. One effective effort to prevent hypothermia is through Early Initiation of Breastfeeding (EIBF) using skin-to-skin contact between mother and baby immediately after birth. Objective: This study aims to determine the effect of Early Initiation of Breastfeeding on the prevention of hypothermia in newborns within the working area of the Pakkat Public Health Center, Pakkat District, Humbang Hasundutan Regency, North Sumatra Province, in 2024. Methods: This study utilized a quasi-experimental design with a One Group Pretest-Posttest Design. The research population consisted of all normal newborns in the working area of Pakkat Public Health Center, totaling 20 infants, with a sample of 12 infants who met the inclusion criteria selected via the total sampling technique. Body temperature measurements were taken before and after EIBF implementation using a digital thermometer. Data analysis was conducted using the Paired Samples T-Test with a 95% confidence level (alpha = 0.05). Results: The average body temperature of the infants increased by 0.68°C after EIBF. The results of the Paired Samples T-Test showed a p-value = 0.000 (p < 0.05), indicating a significant effect of EIBF implementation on increasing the body temperature of newborns. Conclusion: The implementation of Early Initiation of Breastfeeding is effective in increasing newborn body temperature, making it a viable routine intervention in essential neonatal services to prevent hypothermia.